The Erard Grecian Harp in Regency England - Poulopoulos, Panagiotis (Boydell & Brewer, Incorporated, 2023)
Sébastien Erard (1752-1831) was a major force in the technical, musical and visual upgrading of the harp as both a novel instrument and symbol of status.